Climate Change Genomics Calls for Standardized Data Reporting - Waldvogel, Ann-Marie; Schreiber, Dennis; Pfenninger, Markus; Feldmeyer, Barbara (Frontiers in Ecology and Evolution, 2020)
The advent of new and affordable high-throughput sequencing techniques allows for the investigation of the genetic basis of environmental adaptation throughout the plant and animal kingdom. Knowledge on the adaptive potential of organisms, the generality or idiosyncrasy of adaptation patterns and mechanisms is crucial for making predictions about their future persistence potential and/or risk of extinction in a rapidly changing environment. The framework of genotype-environment associations (GEA) provides a powerful link by correlating the geographic distribution of genotype patterns of individuals or populations with environmental factors on a spatial scale. In this review, we coarsely summarize the short history of GEA studies with a main focus on climate variables as environmental factors. While our initial aim was to compare results of existing studies to identify common patterns or differences in climate adaptation, we quickly realized that such a meta-analysis approach is currently unfeasible. Every study is presenting their data and results in a different format, and vast amounts of data have not been deposited in any repository at all. We thus make a strong call for standardized data and reposition structure for GEA studies. Moreover, the coordinated documentation of candidate genes associated to environmental factors could allow the establishment of a new and additional gene ontology domain ‘environmental association’. This would systematically link fitness relevant genes to the corresponding environmental factor.